Gender Bias and the Sex Trafficking Interventions in the Eastern Border of India–Nepal. (September 2019) - Chetry, Pooja; Pande, Rekha
The present article looks at gender bias and sex trafficking interventions in the eastern border of India–Nepal. It attempts to understand the socio-economic conditions and other influencing factors that circumscribe a woman's migration. It documents the interventions by anti-trafficking networks and explores the experience of intercepted women. It attempts to show how interception methods as techniques of intervention to combat trafficking in persons are gender biased. Interception, as a primary method of intervention, is used by anti-trafficking organisations to prevent the occurrence of human trafficking cases in its origin/source country. On suspicion, a woman or a girl crossing the border alone or in all-female groups is stopped and intercepted by the anti-trafficking activists on the ground of her being a potential victim of sex trafficking. Such interception generally takes place within 3 km radius of the border of Panitanki, India, to Kakarbitta, Nepal in order to prevent the unsafe and illegal migration of girls/women. The cross-questioning method is used to extract information and validation about her identity and travel. This article, therefore, examines interception methods as techniques of intervention to combat trafficking in persons. It shows how this intervention method in certain aspect is patriarchal in its form. It reinforces the patriarchal belief of women's vulnerability in the absence of male authority leading to discreet dangers.